All the News That's Fit to Sell : How the Market Transforms Information into News - Hamilton, James, 1961- (Book collections on Project MUSE., 2004)
That market forces drive the news is not news. Whether a story appears in print, on television, or on the Internet depends on who is interested, its value to advertisers, the costs of assembling the details, and competitors' products. But in All the News That's Fit to Sell, economist James Hamilton shows just how this happens. Furthermore, many complaints about journalism--media bias, soft news, and pundits as celebrities--arise from the impact of this economic logic on news judgments. This is the first book to develop an economic theory of news, analyze evidence across a wide.